AN EMPIRICAL STUDY ON ORGANISATIONAL CLIMATE IN SUGAR MILLS OF TAMIL NADU - Chitra, R; Rajakumari, D (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The main aim of the research is to examine the diverse elements that compose organisational climate in the sugar mills of Tamil Nadu. The study is focused on obtaining opinions from the workers working in the sugar mills in the study area of Tamil Nadu. The study has the base of empirical research which is carried out based on the observations in the field. The data was collected using the structure interview schedule which is derived from literature and preliminary investigation in the field. The research follows the methodology adopted in empirical research. The samples used for collecting the data were selected based on random sampling technique. The sample size of the study was fixed to be 209 based on the standard deviation derived from the results of the pilot study. The lists of the population frame were collected from 4 profitable sugar mills that are operating in the study area of Salem District. The collected list were used for randomization of the population out of which 209 workers were selected based on tippet’s table method using simple random sampling. The analysis is composed of confirmatory factor analysis modeling in Analysis of Movement Structure software. The elements of Fair Compensation Policy (FCP), Participative Working Environment (PWE), Supportive Leadership (SL), Workers Welfare and Satisfaction (WWS) and Career Development Practices (CDP) has vital influence on the organisational climate in the sugar mills of Tamil nadu.